Challenges for organismic taxonomical revisions in the age of phylogenomics: A response to Zhang et al. (2019) - Trujano-Ortega, Marysol; Ávalos-Hernández, Omar; Callaghan, Curtis J.; García-Vázquez, Uri Omar; Luis-Martínez, Armando; Llorente-Bousquets, Jorge (Zootaxa, 2020)
Tribe Emesidini Seraphim, Freitas & Kaminski (Lepidoptera: Riodinidae) is distributed in America from southwest Canada to Brazil and Paraguay, and includes 57 species and 54 subspecies (Callaghan & Lamas 2004; Penz & DeVries 2006; Gallard 2008; Pelham 2008; De la Maza & De la Maza 2017 a,b; Kaminski et al. 2017; Seraphim et al. 2018; Trujano-Ortega et al. 2018; Zhang et al. 2019). The tribe has great taxonomic, morphological and ecological diversity, as well as wide geographic and seasonal variation. This great variation and broad geographic range of some genera entail the need for a taxonomic review (Espeland et al. 2015; Trujano-Ortega et al. 2018).